Alkaline molten salt system furnace lining material as well as preparation method, evaluation method and application thereof
By using aluminum ash slag and lightly charred magnesium powder to prepare alkaline molten salt system furnace lining materials, the problems of rapid reaction, environmental pollution and high cost of existing materials in high temperature and chemical erosion environments are solved, and the high temperature stability and corrosion resistance of the materials are improved, which is economic and environmental benefits.
Patent Information
- Application Number
- CN202510091432.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
Existing furnace lining materials have problems of rapid reaction, environmental pollution and high costs in high temperature and chemical erosion environments.
Aluminum ash slag and lightly flammed magnesium powder are used as the main raw materials to prepare alkaline molten salt system furnace lining materials through mixing, press molding and sintering processes. The extensive acquisition and low cost of aluminum ash slag are used to reduce environmental pollution, and the high temperature stability and corrosion resistance of the material are improved through the formation of magnesium-aluminum spinel phase.
The good stability and corrosion resistance of the furnace lining materials in high temperature and chemical erosion environments are achieved, which reduces production costs and environmental burdens, and has significant economic and environmental benefits.
Smart Images

Figure CN119822857A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of alkaline molten salt system furnace lining materials, and in particular relates to an alkaline molten salt system furnace lining material and a preparation method, an evaluation method and an application thereof. Background Art
[0002] Furnace linings refer to one or more layers of materials used inside industrial furnaces to protect the furnace shell and other structural components from harsh environments such as high temperature, chemical erosion, and mechanical impact. It is essential to ensure the efficient operation and extended service life of industrial furnaces.
[0003] In the relevant technology, alumina, magnesia-chrome bricks, zirconium corundum bricks, refractory fibers, etc. are generally used as furnace lining materials. However, alumina may react rapidly with molten salt in some cases, resulting in material degradation. Although magnesia-chrome bricks have excellent high temperature resistance and corrosion resistance, they may cause environmental pollution problems during the production process. Zirconia corundum bricks have good stability but are more expensive. Refractory fibers may lose some of their performance at high temperatures. Summary of the invention
[0004] The purpose of the present application is to provide an alkaline molten salt system furnace lining material and its preparation method, evaluation method and application, which can improve the problems of rapid reaction between the furnace lining material and the molten salt, environmental pollution and high cost.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides an alkaline molten salt system furnace lining material, wherein raw materials for preparing the alkaline molten salt system furnace lining material include aluminum ash slag and light-burned magnesium powder.
[0007] The alkaline molten salt system furnace lining material provided in the present application uses aluminum ash slag as a main raw material. Aluminum ash slag is mainly industrial waste generated in the process of electrolytic aluminum and recycled aluminum industry. At present, the utilization rate of aluminum ash slag is low, and most of it is abandoned and piled up. The loss of aluminum resources will also cause environmental damage. Aluminum ash slag has a wide source of acquisition and low cost. In addition, waste utilization of aluminum ash slag can reduce the pollution of aluminum ash slag generated in industry to the environment. Light-burned magnesium powder is used as another preparation raw material. It is mixed with aluminum in aluminum ash slag to obtain an alkaline molten salt system furnace lining material, which can enable the alkaline molten salt system furnace lining material to maintain good stability in the molten salt system.
[0008] In some embodiments, the mass fraction ratio of the aluminum ash slag and the light-burned magnesium powder in the raw materials for preparing the alkaline molten salt system furnace lining material is 4 to 6:1.
[0009] In some embodiments, the mass fraction ratio of the aluminum ash slag and the light-burned magnesium powder in the raw materials for preparing the alkaline molten salt system furnace lining material is 5:1.
[0010] In some embodiments, the content of magnesium oxide in the light-burned magnesium powder is greater than 90%.
[0011] In a second aspect, the present application provides a method for preparing an alkaline molten salt system furnace lining material, the method comprising:
[0012] The aluminum ash slag is mixed with the light-burned magnesium powder to obtain a mixed powder;
[0013] Pressing the mixed powder into a shape to obtain a green embryo;
[0014] The green embryo is sintered to obtain an alkaline molten salt system furnace lining material.
[0015] The preparation method of alkaline molten salt system furnace lining material provided in the present application has a simple preparation process and is easy to operate. Through the standardization of the preparation process, mass production can be achieved. Aluminum ash slag is used as the main raw material, which reduces the discharge of industrial waste and reduces the environmental burden. The method not only reduces the production cost, but also has significant economic and environmental benefits.
[0016] In some embodiments, before mixing the aluminum ash slag with the light-burned magnesium powder to obtain a mixed powder, the process includes:
[0017] The aluminum ash ash is screened for particle size; wherein the particle size range of the screened aluminum slag ash is 180 μm to 220 μm;
[0018] The screened aluminum ash slag is dried; wherein the drying temperature is 50 to 85°C and the drying time is 15 to 24 hours;
[0019] And / or, in the step of mixing the aluminum ash slag with the light-burned magnesium powder to obtain the mixed powder, the mixing time is 2 to 5 hours;
[0020] And / or, before the mixed powder is pressed into a shape to obtain a green embryo, the preparation method comprises:
[0021] PVP with a mass fraction of 3% is added to the mixed powder.
[0022] In some embodiments, in the step of pressing the mixed powder to obtain a green embryo, the pressing pressure is 25 MPa and the holding time is 1 to 5 minutes;
[0023] And / or, in the step of sintering the green embryo to obtain the alkaline molten salt system furnace lining material, the sintering temperature is 1100-1500° C. and the sintering time is 1-3 hours.
[0024] In a third aspect, the present application provides a method for evaluating an alkaline molten salt system furnace lining material, the method comprising:
[0025] Covering the molten salt material on the alkaline molten salt system furnace lining material to obtain an erosion mixture; the alkaline molten salt system furnace lining material is the alkaline molten salt system furnace lining material prepared by any of the above-mentioned alkaline molten salt system furnace lining material preparation methods;
[0026] The etching mixture is subjected to high-temperature etching to obtain an etched product of an alkaline molten salt system furnace lining material, and the etched product of the alkaline molten salt system furnace lining material is subjected to SEM / EDS analysis.
[0027] The third aspect of the present application provides an evaluation method for alkaline molten salt system furnace lining materials, which covers the molten salt material on the furnace lining material, performs high-temperature corrosion, and then performs SEM / EDS analysis on the eroded material, so as to understand the corrosion resistance, chemical composition changes, and microstructure of the alkaline molten salt system furnace lining material, thereby providing an analysis basis for the corrosion resistance of the alkaline molten salt system furnace lining material.
[0028] In some embodiments, in the step of covering the molten salt material on the alkaline molten salt system furnace lining material to obtain the etching mixture, the molten salt material is NaCl-Na2CO3, and the mass ratio of NaCl, Na2CO3 and the alkaline molten salt system furnace lining material is 1:1:1;
[0029] And / or, in the step of etching the etching mixture to obtain an etched product of an alkaline molten salt system furnace lining material, the etching temperature is 800-1000°C.
[0030] In a fourth aspect, the present application provides an application of an alkaline molten salt system furnace lining material, wherein any of the above-mentioned alkaline molten salt system furnace lining materials, and / or any of the above-mentioned alkaline molten salt system furnace lining materials prepared by the above-mentioned alkaline molten salt system furnace lining material preparation methods are applied to an alkaline molten salt system.
[0031] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0033] Figure 1 It is a schematic flow chart of a method for preparing a furnace lining material in an alkaline molten salt system provided in an embodiment of the present application;
[0034] Figure 2 is an XRD diagram of aluminum ash slag of the alkaline molten salt system lining material provided in the embodiment of the present application;
[0035] Figure 3 is an XRD diagram of the alkaline molten salt system furnace lining material provided in the embodiments of the present application at different sintering temperatures;
[0036] Figure 4 is a SEM image of the alkaline molten salt system furnace lining material provided in the embodiments of the present application at different sintering temperatures;
[0037] Figure 5 It is a surface phase diagram of the alkaline molten salt system furnace lining material provided in the embodiment of the present application at different erosion times;
[0038] Figure 6 It is a line scan of the erosion section of the alkaline molten salt system furnace lining material provided in the embodiment of the present application;
[0039] Figure 7 These are SEM images of different regions of the eroded section of the alkaline molten salt system furnace lining material provided in the examples of the present application. DETAILED DESCRIPTION
[0040] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0041] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0042] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0043] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0044] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0045] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0046] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0047] Furnace linings refer to one or more layers of materials used inside industrial furnaces to protect the furnace shell and other structural components from harsh environments such as high temperature, chemical erosion, and mechanical impact. It is essential to ensure the efficient operation and extended service life of industrial furnaces.
[0048] In the relevant technology, alumina, magnesia-chrome bricks, zirconium corundum bricks, refractory fibers, etc. are generally used as furnace lining materials. However, alumina may react rapidly with molten salt in some cases, resulting in material degradation. Although magnesia-chrome bricks have excellent high temperature resistance and corrosion resistance, they may cause environmental pollution problems during the production process. Zirconia corundum bricks have good stability but are more expensive. Refractory fibers may lose some of their performance at high temperatures.
[0049] Based on this, in order to improve the problems of rapid reaction between furnace lining materials and molten salt, environmental pollution and high cost in the related technology, the embodiments of the present application provide the following solutions.
[0050] In a first aspect, an embodiment of the present application provides an alkaline molten salt system furnace lining material, wherein raw materials for preparing the alkaline molten salt system furnace lining material include aluminum ash slag and light-burned magnesium powder.
[0051] It can be understood that light-burned magnesium powder is a product obtained by calcining natural magnesite (the main component is magnesium carbonate MgCO3) at a certain temperature (e.g. 700-1000°C). Table 1 below is a table of chemical composition elements obtained by atomic fluorescence analysis of aluminum ash slag. Figure 2 The XRD spectrum of aluminum ash slag, aluminum ash slag includes the following chemical components: Al20-25%; Al2O320-25%; MgAl2O48-10%; MgO9-11%; SiO214-16%; CaO4-5%; Fe2O33-4%; Na2O2-3%; TiO22-3%; AlN2-3%, among which aluminum 10-25%, which can be 10%, 20%, 25%, etc., and the same applies to other substances. It should be noted that the MgO obtained by analysis is 5-15%, which means that the content of Mg element is 5-15%. For easy understanding and explanation, the content of each element is replaced by the form of oxide, and other substances are based on this. The sources of aluminum ash slag can include primary aluminum ash, primary aluminum ash regeneration smelting aluminum residue, automotive aluminum scrap / cans / waste aluminum alloy door and window smelting aluminum residue, etc.
[0052] Table 1 Unit: % (mass fraction)
[0053]
[0054] From the above, it can be seen that the alkaline molten salt system furnace lining material provided in the embodiment of the present application uses aluminum ash slag as the main raw material. Aluminum ash slag is mainly industrial waste generated in the process of electrolytic aluminum and recycled aluminum industry. At present, the utilization rate of aluminum ash slag is low, and most of it is abandoned and piled up. The loss of aluminum resources will also cause environmental damage. Aluminum ash slag has a wide source and low cost, and waste utilization of aluminum ash slag can reduce the pollution of aluminum ash slag generated in industry to the environment; and light-burned magnesium powder is used as another preparation raw material. It is mixed with aluminum in aluminum ash slag to obtain alkaline molten salt system furnace lining material, which can make the alkaline molten salt system furnace lining material maintain good stability under the alkaline molten salt system.
[0055] In some embodiments, the mass fraction ratio of aluminum ash slag and light-burned magnesium powder in the preparation raw materials of the alkaline molten salt system furnace lining material is 4-6:1, for example, it can be 4:1, 4.8:1, 5:1, 6:1, etc., but not limited thereto.
[0056] With such arrangement, the mass ratio of aluminum ash slag to light-burned magnesium powder is 4-6:1, which is beneficial to controlling the microstructure and performance of the alkaline molten salt system furnace lining material. Using aluminum ash slag as the main raw material is beneficial to achieving a win-win situation of economic benefits and environmental protection when the performance of the alkaline molten salt system furnace lining material meets the use requirements of the alkaline molten salt system.
[0057] Optionally, in some embodiments, the mass fraction ratio of aluminum ash slag and light-burned magnesium powder in the raw materials for preparing the alkaline molten salt system furnace lining material is 5:1.
[0058] In this way, the aluminum ash slag and light-burned magnesium powder in this ratio are mixed to better promote the formation of magnesium-aluminum spinel phase, which has excellent high-temperature stability and corrosion resistance, and helps to improve the overall performance of the furnace lining material.
[0059] In some embodiments, the content of magnesium oxide in the light-burned magnesium powder is greater than 90%.
[0060] In this way, a magnesium oxide (MgO) content greater than 90% is conducive to promoting the reaction with aluminum (Al) in the aluminum ash to form a magnesium aluminum spinel phase (MgAl2O4). This phase structure is crucial for improving the material's thermal shock stability and resistance to molten salt corrosion.
[0061] A second aspect of the embodiment of the present application provides a method for preparing an alkaline molten salt system furnace lining material, the method comprising:
[0062] S100, mixing aluminum ash slag and light-burned magnesium powder to obtain a mixed powder.
[0063] It is understood that the stirring can be performed by mechanical stirring, such as a mixer, a ball mill and the like.
[0064] S200, pressing the mixed powder into a mold to obtain a green embryo.
[0065] It is understood that during compression molding, the mixed powder is first placed in a mold, and then compressed using a compression molding device such as a hydraulic press or a static press. Those skilled in the art will understand that the mold cavity can be set according to the actual shape of the green embryo to be compressed, and this application does not make a sole limitation on this.
[0066] S300, sintering the green embryo to obtain an alkaline molten salt system furnace lining material.
[0067] It is understandable that a variety of sintering equipment may be used to sinter the green body, such as a tunnel kiln, a shuttle kiln, a vertical furnace, etc., but not limited thereto.
[0068] From the above, it can be seen that the preparation method of the alkaline molten salt system furnace lining material provided in the embodiment of the present application has a simple preparation process and is easy to operate. Through the standardization of the preparation process, mass production can be achieved. The use of aluminum ash slag as the main raw material reduces the discharge of industrial waste and alleviates the environmental burden.
[0069] In some embodiments, before mixing aluminum ash slag with light-burned magnesium powder to obtain a mixed powder, the process includes:
[0070] S10, screening the aluminum ash ash for particle size; wherein the particle size range of the screened aluminum slag ash is 180 μm to 220 μm.
[0071] It is understood that the particle size range is 180 μm to 220 μm, for example, 180 μm, 200 μm, 220 μm, etc., but not limited thereto. A standard sieve with a mesh size of 60 to 80 mesh can be used for screening, and the aluminum ash slag can be screened by mechanical vibration.
[0072] S20, removing iron from the screened aluminum ash.
[0073] It is understood that the iron in the aluminum slag can be removed by a magnetic separator.
[0074] S20, drying the screened aluminum ash slag; wherein the drying temperature is 50-85° C., and the drying time is 15-24 hours.
[0075] It is understood that the drying temperature is 50 to 85°C, for example, 50°C, 70°C, 80°C, etc., but not limited thereto. The drying time is 15 to 24h, for example, 15h, 20h, 24h, etc., but not limited thereto. After the aluminum ash slag is produced, moisture or other objects in the surrounding environment may adhere to the aluminum ash slag. If the aluminum ash slag contains moisture, the moisture may form bubbles during the mixing and pressing process; these bubbles are difficult to be completely discharged during the sintering process, which will cause pores to appear inside the material, reducing the density and mechanical strength of the material. The dried aluminum ash slag powder has better fluidity, is easier to mix and press evenly, and improves processing efficiency and product quality. For example, the aluminum ash slag can be placed in a drying box or other drying equipment for drying.
[0076] Such arrangement, by subjecting the aluminum ash slag to particle size screening (the particle size range of the screened aluminum slag ash is 180μm to 220μm) and drying (the drying temperature is 50 to 85°C, and the drying time is 15 to 24 hours), is conducive to making the particle size of the aluminum ash slag uniform, removing moisture and other volatile substances, and further improving the performance of the alkaline molten salt system furnace lining material.
[0077] In some embodiments, in step S100, aluminum ash slag is mixed with light-burned magnesium powder to obtain a mixed powder, and the mixing time is 2 to 5 hours.
[0078] It can be understood that the mixing time is 2 to 5 hours, for example, 2 hours, 3 hours, 5 hours, etc., but is not limited thereto.
[0079] By controlling the mixing time to 2 to 5 hours, the uniformity of aluminum ash slag and light-burned magnesium powder in the powder can be improved, and the phenomenon of local uneven composition can be reduced. Uniform chemical composition helps to form a more uniform microstructure, thereby improving the overall performance of the material.
[0080] Optionally, in step S200, before the mixed powder is pressed into a shape to obtain a green embryo, the following steps are included:
[0081] Add 3% PVP by mass into the mixed powder.
[0082] It can be understood that PVP is polyvinyl pyrrolidone, which is an organic high molecular polymer.
[0083] In this way, PVP has certain bonding properties, which can enhance the bonding force between powder particles, improve the strength and stability of the green embryo, and reduce breakage during transportation and sintering. At the same time, PVP can decompose at high temperatures, and the released gas can help eliminate the pores in the green embryo, promote densification during the sintering process, and improve the density and mechanical properties of the final product. That is, adding 3% PVP by mass can improve the processing performance of the powder and the performance of the final product.
[0084] In some embodiments, in step S200, the mixed powder is pressed to obtain a green embryo, the pressing pressure is 25 MPa, and the holding time is 1 to 5 minutes.
[0085] It can be understood that the holding time is 1 to 5 minutes, for example, 1 minute, 3 minutes, 5 minutes, etc., but is not limited thereto.
[0086] With this setting, a pressure of 25MPa and a holding time of 1 to 5 minutes can ensure that the pressure is evenly transmitted in the powder, making the density and structure of the entire green embryo more uniform. This helps to reduce cracks and defects that may occur during the sintering process, improve the uniformity and consistency of the material, thereby optimizing the sintering process, improving the mechanical properties and corrosion resistance of the final product, and improving production efficiency and product quality.
[0087] In some embodiments, in step S300, the green body is sintered to obtain an alkaline molten salt system furnace lining material, the sintering temperature is 1100-1500°C, and the sintering time is 1-3 hours.
[0088] It can be understood that the sintering temperature is 1100-1500°C, for example, it can be 1100°C, 1400°C, 1500°C, etc., but not limited thereto. The sintering time is 1-3h, for example, it can be 1h, 2h, 3h, etc., but not limited thereto. At a high temperature of 1100-1500°C, the alumina in the aluminum slag ash and the light-burned magnesium powder can fully react to form magnesium-aluminum spinel. Magnesium-aluminum spinel has a high melting point and good chemical stability, which can significantly improve the mechanical strength and corrosion resistance of the material.
[0089] In this way, by controlling the sintering temperature to 1100-1500°C and the sintering time to 1-3h, a dense alkaline molten salt system furnace lining material with excellent performance can be formed. These parameters can improve the density and uniformity of the alkaline molten salt system furnace lining material and improve the corrosion resistance of the alkaline molten salt system furnace lining material.
[0090] A third aspect of the embodiment of the present application provides a method for evaluating an alkaline molten salt system furnace lining material, the method comprising:
[0091] The molten salt material is covered on the alkaline molten salt system furnace lining material to obtain an etching mixture.
[0092] It is understood that the molten salt powder can be evenly covered on the surface of the sample to obtain the erosion mixture. For example, the molten salt powder can be evenly covered on the surface of the sample by using a tool (such as a scraper, a brush, etc.).
[0093] The etching mixture is subjected to high temperature etching to obtain an etched product of an alkaline molten salt system furnace lining material, and the etched product of the alkaline molten salt system furnace lining material is subjected to SEM / EDS analysis.
[0094] It can be understood that SEM-EDS analysis refers to the use of Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) to conduct a detailed analysis of the microstructure and chemical composition of the eroded product.
[0095] From the above, it can be seen that the evaluation method of alkaline molten salt system lining materials provided in the embodiment of the present application can comprehensively evaluate the corrosion resistance, chemical composition changes, and microstructure of the material by covering the molten salt material on the lining material, performing high-temperature corrosion, and then performing SEM / EDS analysis on the eroded material. This method has the technical effects of accurately evaluating corrosion resistance, optimizing material design, improving reliability, reducing test costs, comprehensively evaluating material performance, improving experimental repeatability, adapting to a variety of molten salt systems, and being environmentally friendly, and provides a scientific basis for the research and development and application of alkaline molten salt system lining materials.
[0096] Optionally, in some embodiments, when the molten salt material is covered on the alkaline molten salt system furnace lining material to obtain the etching mixture, the molten salt material is NaCl-Na2CO3, and the mass ratio of NaCl, Na2CO3 and the alkaline molten salt system furnace lining material is 1:1:1.
[0097] It is understandable that the NaCl-Na2CO3 molten salt system is common in many high-temperature industrial applications, such as solar thermal power generation, chemical processes, etc. By using this molten salt system, the actual application conditions can be simulated more realistically and the corrosion resistance of the furnace lining material in actual use can be evaluated.
[0098] In this way, the molten salt material is set to NaCl-Na2CO3, and the mass ratio of NaCl, Na2CO3 and alkaline molten salt system lining material is 1:1:1, which can ensure the uniform coverage of the molten salt material, provide standard test conditions, simulate actual applications, improve evaluation accuracy, optimize material design, reduce test costs, and have environmentally friendly characteristics. This method provides a scientific basis for the performance evaluation of alkaline molten salt system lining materials and helps to improve the corrosion resistance and reliability of materials.
[0099] Optionally, in some embodiments, when etching the etching mixture to obtain an etched product of the alkaline molten salt system furnace lining material, the etching temperature is 800-1000°C.
[0100] It is understood that the corrosion temperature is 800-1000°C, for example, it can be 800°C, 900°C, 1000°C, etc., but not limited thereto. In the temperature range of 800-1000°C, the molten salt material (such as NaCl-Na2CO3) will undergo complex chemical reactions to generate more corrosive compounds, simulating the corrosion mechanism in actual applications and evaluating the performance of the furnace lining material in a complex corrosive environment.
[0101] A third aspect of the embodiments of the present application provides an application of an alkaline molten salt system furnace lining material, wherein the alkaline molten salt system furnace lining material of any of the above embodiments is applied to an alkaline molten salt system.
[0102] It can be understood that the alkaline smelting system refers to a smelting furnace that uses alkaline molten salts (such as NaOH, KOH, NaCl, Na2CO3, K2CO3, etc.) for smelting.
[0103] The following describes the invention in conjunction with specific embodiments.
[0104] Example 1
[0105] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 200 μm, and then dried at a drying temperature of 70° C. for 20 h for later use.
[0106] (2) Weigh 2.0 g of light-burned magnesium powder and 10.0 g of aluminum ash slag and mix them for 3 hours to obtain a mixed powder.
[0107] (3) 0.37 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was pressurized for 3 min at a molding pressure of 25 MPa on a hydraulic molding machine to obtain a cylindrical green body.
[0108] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 1400° C. and sintered for 3 hours to obtain an alkaline molten salt system furnace lining material.
[0109] (5) 12.0 g of NaCl and 12.0 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 900°C for 2 h. The maximum erosion depth was measured to be 3.80 mm.
[0110] Example 2
[0111] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 180 μm, and then dried at a drying temperature of 50° C. for 15 h for later use.
[0112] (2) Weigh 2.0 g of light-burned magnesium powder and 8.0 g of aluminum ash slag and mix them for 2 hours to obtain a mixed powder.
[0113] (3) 0.31 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was kept under a molding pressure of 25 MPa in a hydraulic molding machine for 1 min to obtain a cylindrical green body.
[0114] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 1100° C. and sintered for 2 h to obtain an alkaline molten salt system furnace lining material.
[0115] (5) 10.0 g of NaCl and 10.0 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 800°C for 2 h. The maximum erosion depth was measured to be 3.91 mm.
[0116] Example 3
[0117] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 220 μm, and then dried at a drying temperature of 85° C. for 24 h for later use.
[0118] (2) Weigh 2.0 g of light-burned magnesium powder and 12.0 g of aluminum ash slag and mix them for 5 hours to obtain a mixed powder.
[0119] (3) 0.43 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was pressurized at a molding pressure of 25 MPa on a hydraulic molding machine for 5 min to obtain a cylindrical green body.
[0120] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 1500° C. and sintered for 1 hour to obtain an alkaline molten salt system furnace lining material.
[0121] (5) 14.0 g of NaCl and 14.0 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 1000°C for 2 h. The maximum erosion depth was measured to be 3.85 mm.
[0122] Comparative Example 1
[0123] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 500 μm, and then dried at a drying temperature of 70° C. for 20 h for later use.
[0124] (2) Weigh 2.0 g of light-burned magnesium powder and 15.0 g of aluminum ash slag and mix them for 2 hours to obtain a mixed powder.
[0125] (3) 0.52 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was pressurized at a molding pressure of 25 MPa on a hydraulic molding machine for 3 min to obtain a cylindrical green body.
[0126] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 1400° C. and sintered for 3 hours to obtain an alkaline molten salt system furnace lining material.
[0127] (5) 17.0 g of NaCl and 17.0 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 900°C for 2 h. The maximum erosion depth was measured to be 6.77 mm.
[0128] Comparative Example 2
[0129] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 200 μm, and then dried at a drying temperature of 70° C. for 20 h for later use.
[0130] (2) Weigh 5.0 g of light-burned magnesium powder and 5.0 g of aluminum ash slag and mix them for 3 hours to obtain a mixed powder.
[0131] (3) 0.30 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was pressurized at a molding pressure of 25 MPa on a hydraulic molding machine for 3 min to obtain a cylindrical green body.
[0132] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 1400° C. and sintered for 3 hours to obtain an alkaline molten salt system furnace lining material.
[0133] (5) 10 g of NaCl and 10 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 900 °C for 2 h. The maximum erosion depth was measured to be 7.52 mm.
[0134] Comparative Example 3
[0135] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 200 μm, and then dried at a drying temperature of 70° C. for 20 h for later use.
[0136] (2) Weigh 2.0 g of light-burned magnesium powder and 10.0 g of aluminum ash slag and mix them for 3 hours to obtain a mixed powder.
[0137] (3) 0.37 g of PVP was added to the mixed powder, and after uniform mixing, the mixed powder was pressurized for 3 min at a molding pressure of 25 MPa on a hydraulic molding machine to obtain a cylindrical green body.
[0138] (4) The cylindrical green body is placed in a high-temperature sintering tube furnace, the sintering temperature is controlled to be 900° C. and sintered for 5 hours to obtain an alkaline molten salt system furnace lining material.
[0139] (5) 12.0 g of NaCl and 12.0 g of Na2CO3 were mixed and used to cover the alkaline molten salt system furnace lining material. The mixture was then placed in a corundum crucible and etched at 900°C for 2 h. The maximum erosion depth was measured to be 7.55 mm.
[0140] It can be seen from the above that, based on the comparative analysis of the maximum erosion depth, the alkaline molten salt system furnace lining material prepared in the present application has good corrosion resistance.
[0141] The following is an analysis and evaluation of the performance of the furnace lining material in the alkaline molten salt system. The aluminum ash slag was taken from the slag on the molten aluminum in the smelting furnace of a recycled aluminum enterprise in Jiangxi.
[0142] (1) The aluminum ash slag is sieved to obtain aluminum ash slag with a particle size of 200 μm, and then dried at a drying temperature of 70° C. for 20 h for later use.
[0143] (2) Weigh 5 parts of 8.333 g of aluminum ash slag and 5 parts of 1.667 g of light-burned magnesium powder, and use a mixer to mix the aluminum ash slag and the light-burned magnesium powder for 3 hours to obtain 5 parts of mixed powder.
[0144] (3) 0.3 g of PVP was added to 5 portions of the mixed powder respectively. After uniform mixing, the mixed powder was pressurized at 25 MPa for 3 min on a hydraulic molding machine. Five portions of cylindrical green bodies with a height of 1 cm and a diameter of 2.5 cm were prepared by demolding.
[0145] (4) Five cylindrical green bodies were placed in a high-temperature sintering tube furnace respectively, and the sintering temperatures were controlled to be 1100°C, 1200°C, 1300°C, 1400°C and 1500°C for 3 h respectively to prepare five alkaline molten salt system furnace lining materials. XRD analysis and SEM analysis were performed on the five alkaline molten salt system furnace lining materials.
[0146] (5) Take 5 parts of 10g NaCl and 10g Na2CO3, mix them respectively, and then cover 5 parts of alkaline molten salt system furnace lining materials obtained at different sintering temperatures.
[0147] (6) The alkaline molten salt system furnace lining material was prepared by sintering at a sintering temperature of 1400°C for 3 hours and placed in a corundum crucible and etched at 900°C for 2 hours, 5 hours and 10 hours. After cooling, the corrosion materials at different erosion times were analyzed respectively. The sample cross-section analysis pretreatment, the sample was coarsely ground, finely ground, and polished to obtain a flat, smooth, and clean surface. The surface of the ground sample was gold-sprayed for SEM / EDS analysis.
[0148] like Figure 3 and Figure 4 As shown, Figure 3 XRD of furnace lining materials of alkaline molten salt system at different sintering temperatures, among which 1 is magnesia-alumina spinel; 2 is Al2O3; 3 is Mg2SiO4. The phases of the system at 1100℃ are magnesia-alumina spinel, Mg2SiO4 and unreacted Al2O3. The phases of the system at 1200℃ are magnesia-alumina spinel, Al2O3 and Mg2SiO4 disappear. Above 1200℃, the main phase of the system is magnesia-alumina spinel, and no other obvious phases are seen. The diffraction peak intensity of magnesia-alumina spinel of the 1300℃ sample is higher than that of 1200℃, and the crystallization strength of magnesia-alumina spinel is higher. The diffraction peak intensity of magnesia-alumina spinel of the 1500℃ sample does not show a significant increase. Figure 4 This is the SEM of the alkaline molten salt system lining material at different sintering temperatures, where: Figure 4 The sintering temperature corresponding to a is 1100℃, the sintering temperature corresponding to b is 1200℃, the sintering temperature corresponding to c is 1300℃, the sintering temperature corresponding to d is 1400℃, and the sintering temperature corresponding to e is 1500℃. It can be seen that under the sintering temperature of 1100-1500℃, the material powder crystals are obviously arranged tightly, among which the magnesia-alumina spinel crystals sintered at 1400℃ are tightly arranged and the particle size is uniform.
[0149] like Figure 5 As shown, Figure 5This is the phase analysis of the surface of the furnace lining material in the alkaline molten salt system under different erosion times, where 1 is magnesia-alumina spinel; 2 is NaCl; 3 is Na2CO3. It can be seen from the figure that the main phase of the blank sample is magnesia-alumina spinel. After erosion at 900℃ for 2 hours, the main phases of the material are magnesia-alumina spinel and NaCl, and the magnesia-alumina spinel is obvious. After erosion for 5 hours, the main phase of the material is NaCl, and the characteristic peak of magnesia-alumina spinel is no longer obvious, indicating that the relative content of magnesia-alumina spinel in the test material is very small. After erosion for 10 hours, the main phases of the material are NaCl and Na2CO3, and magnesia-alumina spinel no longer exists, indicating that the MA material prepared by sintering aluminum ash slag is eroded in the NaCl-Na2CO3 system for 10 hours, and the material is eroded more completely.
[0150] like Figure 6 As shown, Figure 6 The line scan of the material erosion section shows that the Na content is high in the erosion area, and is basically absent in the base of the material. This is the mass transfer process of molten salt erosion. The changes in Mg and Al elements are not obvious. This may be because the erosion process causes the reaction of magnesium-aluminum spinel + Na2CO3 = MgCO3 + 2NaAlO2, which makes Mg and Al elements still remain in the material. There are three regions in the erosion process of NaCl-Na2CO3 on the lining material of the alkaline molten salt system, namely the erosion area, transition area and base area, as shown in Tables 2 to 4 below. Table 2 shows the EDS element content in the erosion area of the material section, Table 3 shows the EDS element content in the transition area of the material section, and Table 4 shows the EDS element content in the matrix area of the material section.
[0151] Table 2
[0152]
[0153] Table 3
[0154]
[0155]
[0156] Table 4
[0157]
[0158] like Figure 7 As shown, Figure 7 Schematic diagram of SEM analysis of different areas of the material cross section, where: Figure 7The A area is mainly porous and loose, and the B area is mainly the base of the material. The microstructure is tighter than the eroded area. A1~A4 are the microstructures of the eroded area A of the material at different magnifications. The eroded area is no longer an octahedral magnesium-aluminum spinel structure, but has transformed into a ball-like agglomerate. B1 is the microstructure of the base area B of the material at magnification. The material microstructure maintains a well-uniform and densely arranged octahedral structure. At the same time, the erosion depth of the organization was measured. The results show that the alkaline molten salt system lining material is corroded at 900℃ for 2h in the NaCl-Na2CO3 molten salt system, with a maximum erosion depth of 3.8mm and an average erosion depth of 3.32mm, which has good corrosion resistance and stability.
[0159] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. An alkaline molten salt system furnace lining material, characterized in that: The raw materials for preparing the alkaline molten salt system furnace lining material include aluminum ash slag and light-burned magnesium powder.
2. The alkaline molten salt system furnace lining material according to claim 1, characterized in that: The mass fraction ratio of the aluminum ash slag and the light-burned magnesium powder in the raw materials for preparing the alkaline molten salt system furnace lining material is 4 to 6:
1.
3. The alkaline molten salt system furnace lining material according to claim 2, characterized in that: The mass fraction ratio of the aluminum ash slag and the light-burned magnesium powder in the raw materials for preparing the alkaline molten salt system furnace lining material is 5:
1.
4. The alkaline molten salt system furnace lining material according to claim 1, characterized in that: The content of magnesium oxide in the light-burned magnesium powder is greater than 90%.
5. A method for preparing an alkaline molten salt system furnace lining material, characterized in that: The method for preparing the alkaline molten salt system furnace lining material comprises: The aluminum ash slag is mixed with the light-burned magnesium powder to obtain a mixed powder; Pressing the mixed powder into a shape to obtain a green embryo; The green embryo is sintered to obtain an alkaline molten salt system furnace lining material.
6. The method for preparing a furnace lining material for an alkaline molten salt system according to claim 5, characterized in that: Before mixing the aluminum ash slag with the light-burned magnesium powder to obtain a mixed powder, the method comprises: The aluminum ash ash is screened for particle size; wherein the particle size range of the screened aluminum slag ash is 180 μm to 220 μm; The screened aluminum ash is subjected to iron removal treatment; The screened aluminum ash slag is dried; wherein the drying temperature is 50 to 85°C and the drying time is 15 to 24 hours; And / or, in the step of mixing the aluminum ash slag with the light-burned magnesium powder to obtain the mixed powder, the mixing time is 2 to 5 hours; And / or, before the mixed powder is pressed into a shape to obtain a green embryo, the preparation method comprises: PVP with a mass fraction of 3% is added to the mixed powder.
7. The method for preparing a furnace lining material for an alkaline molten salt system according to claim 5, characterized in that: In the step of pressing the mixed powder to obtain a green embryo, the pressing pressure is 25 MPa and the holding time is 1 to 5 minutes; And / or, in the step of sintering the green embryo to obtain the alkaline molten salt system furnace lining material, the sintering temperature is 1100-1500° C. and the sintering time is 1-3 hours.
8. A method for evaluating furnace lining materials in an alkaline molten salt system, characterized in that: The alkaline molten salt system furnace lining material evaluation method comprises: Covering the molten salt material on the alkaline molten salt system furnace lining material to obtain an erosion mixture; the alkaline molten salt system furnace lining material is the alkaline molten salt system furnace lining material prepared by the method for preparing the alkaline molten salt system furnace lining material according to any one of claims 5 to 7; The etching mixture is subjected to high-temperature etching to obtain an etched product of an alkaline molten salt system furnace lining material, and the etched product of the alkaline molten salt system furnace lining material is subjected to SEM-EDS analysis.
9. The method for evaluating alkaline molten salt system furnace lining materials according to claim 8, characterized in that: In the step of covering the molten salt material on the alkaline molten salt system furnace lining material to obtain the erosion mixture, the molten salt material is NaCl-Na2CO3, and the mass ratio of NaCl, Na2CO3 and the alkaline molten salt system furnace lining material is 1:1:1; And / or, in the step of etching the etching mixture to obtain an etched product of an alkaline molten salt system furnace lining material, the etching temperature is 800-1000°C.
10. An application of an alkaline molten salt system furnace lining material, characterized in that: The alkaline molten salt system lining material according to any one of claims 1 to 4, and / or the alkaline molten salt system lining material prepared by the method for preparing the alkaline molten salt system lining material according to any one of claims 5 to 7, is applied to an alkaline molten salt system.
Citation Information
Cited By
Method for synergistically extracting salt from waste incineration fly ash and aluminum ash residues and increasing salt value of waste incineration fly ash and aluminum ash residues
CN121624208A